Medullary thyroid carcinoma with double negative calcitonin and CEA: a case report and update of literature review - Gambardella, Claudio (BMC Endocr Disord, 2019)
BACKGROUND: Medullary thyroid carcinoma is a malignant uncommon and aggressive tumour of the parafollicular C cells. In about 75% of cases it is sporadic while, in case of RET mutation, it is associated to multiple endocrine neoplasia type 2 (25% of cases). The biochemical features of medullary thyroid carcinoma include the production of calcitonin and carcinoembryogenic antigen. The above-mentioned features are useful in the diagnostic process as well as in the follow up and in the prognostication of the disease. Even if calcitonin elevation is strongly associated to MTC, it can also be found increased in many pathological different conditions as pregnancy, lactation, C-cells hyperplasia, autoimmune thyroiditis, end stage renal disease, lung and prostate cancer and several neuroendocrine tumours. Major medullary thyroid tumours are usually connected to high doses of circulating calcitonin, in fact non-secretory variants have hardly been described. CASE PRESENTATION: We herein report the case of a 59 years old male, who had undergone total thyroidectomy for multinodular goiter with negative preoperative calcitonin, showing medullary thyroid carcinoma at definitive pathology. To the best of our knowledge, this is the first case documenting a non-secretory medullary thyroid carcinoma, with double negative markers at the time of diagnosis and at the relapse. CONCLUSION: A Literature review underlining pathological hypothesis, differential diagnosis and alternative and innovative biomarkers to identify non-secretory medullary thyroid carcinoma was carried out.